PENGARUH KEBIJAKAN DIVIDEN, TAX AVOIDANCE DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) SELAMA PERIODE TAHUN 2018-2022 - Istikhomah; Jarno (Jurnal Nusa Akuntansi, 2024)
This research aims to analyze the influence of dividend policy, tax avoidance and asset structure on capital structure. This research was conducted by analyzing the financial reports of companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The sample used in this research was 24 non-cyclical consumer sector companies listed on the Stock Exchange Indonesia (BEI) during the period 2018 to 2022 using purposive sampling techniques. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The panel data regression method was used as the research methodology in this study. Analysis of research results using Eviews 12 Student Version Lite software. The results of this research show that Dividend Policy partially influences Capital Structure. Tax Avoidance partially has no effect on Capital Structure, Asset Structure partially has an effect on Capital Structure and simultaneously Dividend Policy, Tax Avoidance and Asset Structure have an effect on Capital Structure.